Operating Efficiency, Macroeconomic Variables, and Profitability: Evidence from Nepalese Commercial Banks - Poudel, Ramesh (Journal of Nepalese Business Studies, 2023)
This research examines the impact of operating leverage and macroeconomic variables on profitability of Nepalese commercial bank. To measure operating efficiency, and profitability of bank, the researcher uses descriptive cum causal research design with quantitative data from secondary sources. This study employs ordinary least square model using 120 observations of 20 commercial banks as entire population from the period of 2016/17 to 2021/22. This study reveals that the positive influence of operating income ratio, assets utilization ratio, overhead efficiency ratio and interest revenue ratio to the return on assets, return on equity and earning per share of banks. However, the provision for loan losses ratio has negative significant influence to the return on assets, return on equity and earning per share of Nepalese commercial banks. The growth rate of gross domestic product has positive influence to the earning per share of banks but there is insignificant relationship with return on assets and return on equity. Careful selection of lending areas, expanding the size and scope of the operation activities stand out as key avenues for increasing operating efficiency and profitability. The banks might adopt the strategy of diversifying lending portfolio, introduce non-interest income generation program along with increases the size and operation of the activities. The study lacks consideration of debt capital ratio, dividend ratio, interest spread rate, national consumption, government rules and regulation, managerial structure which also influence the profitability and operating efficiency of banks. Future research aims to use structural equation modeling with addressing uncover variables.